Broken coronary stent catheter retrieval percutaneously case report and literature review - Evliya Akdeniz; Baris Yaylak; Gönül Zeren; Ilhan Ilker Avci; Baris Simsek; Tolga Onuk; Can Yücel Karabay (International Journal of the Cardiovascular Academy, 2019)
We present a 73-year-old male patient with an unusual complication of a broken coronary stent catheter during percutaneous coronary angioplasty, which was successfully retrieved by balloon trapping and pulling-back method, along with literature review of similar cases.